Comparative Morphology of the Humerus of Rabbit, Guinea Pig and Mongoose - Shunmugam, Rajathi; Sundaram , Muthukrishnan (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
In this study, six animals of each rabbit, guinea pig and mongoose were used to compare the morphological features of the humerus.  The biometrical parameters of the humerus, viz., mean length, width and circumference at the proximal extremity, distal extremity, and  shaft were studied. In proximal extremity, anteriorly, the head of the rabbit humerus was comparatively thicker as compared to guinea  pig and mongoose. The lateral tuberosity was large and less clearly divided in mongooses and the division was not visible in guinea  pigs and rabbits. The lateral surface of the lateral tuberosity was found with a notch that was deep in mongooses and shallow in rabbit  and guinea pig. The bicipital groove was very deep in guinea pig, less deep in rabbit and shallow in mongooses. The lateral surface of  the shaft was spiral, smooth, and with musculo-spiral groove which was deep in mongooses, shallow in rabbit, and the groove was not  visible in the guinea pig. On the lateral surface of the mongoose's proximal extremity of the humerus, the deltoid tuberosity was found  sharp but in rabbit and guinea pig, it was blunt. The coronoid and olecranon fossa were deep in all the three species studied, but was  found to be prominent in rabbit and guinea pig when compared to mongoose. Mongoose humerus was observed with an additional  supracondylar foramen in the medial surface of distal one fourth of the shaft above the supratrochlear foramen.
Keywords: Biometry; Guinea pig; Humerus; Mongoose; Morphology; Rabbit